Fabrication of Nitride Thin Films on Si Substrates by Atomic Layer Deposition Technique. (26th February 2018) - Ogawa, Shumpei; Kuroda, Tatsuya; Koike, Ryuga; Ishizaki, Hiroki
Abstract: Recently, Plasma Assisted Atomic Layer Deposition Technique will easily control the thickness and the composition of semiconductor films. The radical generated by using the plasma techniques, gave the decrease of the defect into the semiconductor films. In this investigation, the relationship between microwave plasma power, nitrogen gas flow rate and concentration of generated nitrogen radical, was evaluated. At the first, Plasma emission spectrum at microwave plasma power (0 to 400W) was measured using a mixed 200sccm argon gas and 10sccm nitrogen gas. Next, the plasma emission spectrum was measured in the mixing of nitrogen gas flow rate (0 to 40sccm) with 200sccm argon gas flow rate. At that time, the microwave plasma power was set to 200W. Nitrogen radical spectrum were identified from all the emission spectrum, and the nitrogen radical intensity was calculated. As a result, the nitrogen radical intensity became the largest at 200sccm argon gas flow rate and 10sccm nitrogen gas flow rate. In addition, the nitrogen radical intensity increased in proportion to the microwave plasma power. The concentration of generated nitrogen radical could be controlled by changing the microwave plasma power and the nitrogen gas flow rate. Mentioned above, nitride thin films will be obtained on Si Substrates by microwave generated remote plasma assisted atomic layer deposition technique.